Regional Governance and Policy-Making in South America - Hoffmann, Anne Marie. author. aut Link
XXIII, 199 p. 4 illus.
Keywords: This book analyzes Latin American regional integration with a novel conceptual approach grounded in extensive field research. Using the UNASUR (Unión de Naciones Suramericanas) as a case study, the author investigates the process of policy-making in regional public policy fields in South America. The project focuses on intergovernmental structures of regional organizations as an institutional framework for a variety of independent processes in regions. It also challenges the perspective of democratic states as unitary actors and seeks to analyze the factors which favor or obstruct regional processes in different policy-fields. This work will appeal to researchers, graduate students and anyone interested in Latin American politics and policy-making. Anne Marie Hoffmann is Deputy Head at Research and Transfer Centre "Sustainability and Climate Change Management" in Hamburg, Germany.